Role of Culture in the Finnish-Indian Business Negotiations - Suraj, Prabha (My University, 2004)
This research seeks to examine the influences of culture in the face-to-face interaction phase of the business negotiation process between the Indian and the Finnish businessmen. Culture is a complex and intricate phenomena. The negotiation process itself is multi-faceted and culture affects each and every stage of the process. Culture has high relevance and bearing in international negotiations. Putting it simply, culture affects the way people think, act, eat, drink, buy, live, behave and negotiate. A wide array of existing literature on cultural factors and cross-cultural negotiation issues are examined and referred to in this thesis, in an attempt to arrive at the important factors that have an impact on the face-to-face business negotiation process and are influenced by a person’s culture. These factors range from socializing aspect, communication type and time orientation, to behaviour/mannerisms, efficiency levels and decision making customs, covering a broad range of discourses in cross-cultural negotiations. The research work has been designed as a qualitative, inductive, multi-case study used mainly for descriptive purpose. The qualitative research comprises of 13 personal, face-to-face, standardized, interviews of Finnish and Indian business persons from Wärtsilä Finland Oy and Wärtsilä India Ltd. Questions are based on fourteen select topics to investigate into negotiation factors that are influenced by culture. The findings indicate that Indian negotiators essentially displayed qualities of a polychronic, high-context, relationship/people oriented, expressive, hierarchical and formal business culture, while Finnish negotiators displayed qualities of a monochronic, low-context, deal/task-oriented, reserved, egalitarian and informal business culture. The findings denote that cultural differences can influence business negotiations in significant and unexpected ways. These differences arise from deep-seated cultural tendencies that influence the way people interact.
Keywords: Culture; Negotiations; Cross-cultural; Indian negotiator; Finnish negotiator; fi=Markkinointi|en=Marketing|